Peeler Machine for Various Bulbs Equipped with Automatic Washers - Arifani Catri Mutia; Ade Priyo Widhikdho (Journal of World Conference (JWC), 2020)
The herbal medicine production process starts from the preparation and stripping of raw materials, then washing, processing into herbal medicine, and packaging. Priority issues for herbal medicine production are found in the process of stripping old herbal ingredients. This is because the process of stripping raw materials of irregular herbs still uses conventional and traditional methods, namely with a knife. Based on the problem of herbal medicine production, we raised the title of the Peeler Machine of Various Bulbs Equipped with Automatic Washers. The stripping process on this machine uses a rotary system that utilizes the centrifugal force on the peeler pan and then the tubers rotate clockwise then hit the wall and the floor of the peeler is aided by water sprayed by water washer, the skin from the stripping process will fall towards the filter, water used for the process will be recirculated during the process until completion.